Application Of Health Detector (AHD) Dalam Mendeteksi Kesehatan Tubuh Berbasis Android - Ade Silvia Handayani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Wireless Body Area Network (WBAN) is an electronic device that uses a sensor network method to be applied in medical equipment. In recent years, interest in WBAN has increased as it has become an important research area. This study will design the Application Of Health Detector (AHD) android application to detect body health. The application created has succeeded in automatically detecting body health by displaying the value of each sensor reading, namely body temperature, heart rate, blood pressure, and oxygen levels in the blood. This technology provides a remote health monitoring system in real-time. Through the use of sensor nodes on the human body to detect body health and send it to the server and display the body's health status on the android application in healthy detection, indication or need for action. It is hoped that this health detection application can make it easier for people to know the condition of their body's health.